Mildly hydrophobic biobased mulch: A sustainable approach to controlling bare soil evaporation - Barnes, J. L. (2020)
The water drop penetration time (WDPT) was used to assess the hydrophobicity of fresh PSO‐coated sands; the saturated hydraulic conductivity (Ks) and particle density (ρs) were measured as well. The WDPT was also tested on MS‐PSO and CS‐PSO samples aged in four separate environmental conditions for 20–21 d. Both PSO‐coated sands were mildly hydrophobic, and the surface treatment layers reduced evaporative loss by 83–96% over bare soil, which is similar to previous work using extremely hydrophobic chemically treated sands. Freshly coated MS‐PSO had a higher WDPT score and lower Ks than CS‐PSO. After the environmental aging tests, the MS‐PSO and CS‐PSO samples remained mildly hydrophobic. Notably, CS‐PSO had a low initial WDPT (∼1.09 to ∼2.58 s) and a high Ks (2.66 × 10−1 cm s−1), suggesting coarse PSO‐coated sands will permit infiltration. Given these findings, PSO‐coated sand has the potential to be developed into a sustainable alternative to polyethylene film mulch.